Broadband and High‐Sensitivity Time‐Resolved THz System Using Grating‐Assisted Tilted‐Pulse‐Front Phase Matching. Issue 1 (19th October 2021) - Cui, Wei; Awan, Kashif Masud; Huber, Rupert; Dolgaleva, Ksenia; Ménard, Jean‐Michel
Abstract: A broadband and sensitive time‐resolved terahertz (THz) configuration relying on noncollinear optical interactions is presented. This noncollinear scheme enables a higher THz generation and detection efficiency in nonlinear crystals. The concept relies on a pair of thick (2 mm) GaP crystals with a phase grating etched on their surface to achieve phase matching between a diffracted near‐infrared pulse and a THz wave propagating at normal incidence. This system is compared to a standard collinear scheme based on thin (0.2 mm) crystals and, while both systems provide access to a spectral bandwidth extending up to 6.5 THz, it is found that the noncollinear configuration improves the THz signal by more than a factor of 400 and the dynamic range of the system by 30 dB at a frequency of 3 THz. Abstract : A broadband and high‐sensitivity time‐resolved terahertz (THz) system is demonstrated. The concept relies on a phase grating etched at the surface of both the THz generation and detection crystals. This configuration covers a large spectral bandwidth, extending up to 6.5 THz, and increases the spectral intensity by more than 400 times around 3 THz.